Application of Natural Polymers as Excipients in Dosage Forms - A. V. S. Rajeswari; P. Sailaja (Novel Aspects on Pharmaceutical Research Vol. 8, 2023)
The review focuses on the polymers of natural origin and their gaining importance. Natural polymers, which can be found in both woody and non-woody plant components such as bark, seeds, sap, roots, rhizomes, fruits, leaves, and plant gums, are typically polymeric polysaccharides. Natural polymers are widely utilised, have fewer adverse effects, are biodegradable, increase bioavailability, are inexpensive, are readily available, and can be used in a variety of dosage forms. The paper focuses on an overview of natural polymers, their characteristics, chemical components, and applications as excipients in dosage forms. Natural polymers have also importance in controlled and sustained release studies. The non harmful nature of these natural products is advantageous and classified and mentioned.